Mekanisme Implementasi Merdeka Belajar Kampus Merdeka pada Program Studi di Perguruan Tinggi Keagamaan Kristen - Rifky Serva Tuju; Dinn Wahyudin; Laksmi Dewi (LOGON ZOES: Jurnal Teologi, Sosial dan Budaya, 2022)
Independent Learning Merdeka Campus is designed so that Indonesia has superior Human Resources. MBKM is also designed so that students have the freedom to study in higher education. The MBKM Implementation Mechanism will assist Christian religious universities in implementing the MBKM design from the Ministry of Education and Culture so that a proper and correct MBKM management plan is realized. The MBKM Implementation Mechanism in Study Programs at Christian religious universities can also help Christian religious colleges in preparing MBKM implementation in their respective universities. AbstrakMerdeka Belajar Kampus Merdeka dirancang agar Indonesia memiliki Sumber Daya Manusia yang unggul. MBKM dirancang juga agar pelajar memiliki kemerdekaan dalam belajar di Perguruan Tinggi. Mekanisme Implementasi MBKM akan membantu Perguruan Tinggi keagamaan Kristen dalam menerapkan rancangan MBKM dari Kemendikbud sehingga terwujud-nya sebuah rancangan tata kelola MBKM dengan baik dan benar. Mekanisme Implementasi MBKM pada Program Studi di PT keagamaan Kristen ini juga dapat membantu Sekolah Tinggi keagamaan Kristen dalam menyusun Implementasi MBKM di Perguruan Tinggi masing-masing